The Effect of Performance on Reinsurance Decisions of Indonesian General Insurance Companies: An Empirical Review of the Pandemic and Post Pandemic Period - Helena Nadine Hapsari; Lukman Hanif Arbi (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze the effect of ROE on REINS of general insurance companies in Indonesia, comparing the pandemic period (2020–2022) and the post-pandemic period (2023–2024). Using panel data from 50 companies over the 2020–2024 period (250 observations), this study employs three empirical models: Model 1 (2SLS two-way fixed effect with insurance leverage as instrument), Model 2 (OLS one-way fixed effect with contemporaneous ROE), and Model 3 (OLS one-way fixed effect with a one-period lag of ROE). Estimation results show that in Model 1 and Model 2, ROE has no significant effect on REINS. In Model 3, the lag of ROE has a positive coefficient (0.01967) and is significant at the 10% level (p = 0.074), which does not support the underinvestment hypothesis. Financial leverage consistently shows a positive effect, while premium growth consistently shows a negative effect. Comparative period analysis reveals that during the pandemic, the lag of ROE is not significant, whereas in the post-pandemic period, the lag of ROE becomes positive (0.199) and significant (p = 0.009). The Chow test yields a p-value of 0.05758, significant at the 10% level. Model 3 is selected as the main model as it better reflects the real-world decision-making process. This study concludes that the effect of ROE on REINS in Indonesia differs from previous findings, and that the relationship pattern changed after the pandemic. These findings have implications for insurance company management and regulators in formulating reinsurance strategies based on past performance, leverage, and premium growth.